High resolution Chromosomal Microarray Analysis (CMA) enhances the genetic profile of pediatric B-cell Acute Lymphoblastic Leukemia patients. (August 2019) - Mitrakos, Anastasios; Kattamis, Antonis; Katsibardi, Katerina; Papadhimitriou, Stefanos; Kitsiou-Tzeli, Sophia; Kanavakis, Emmanuel; Tzetis, Maria
Highlights: Clinically relevant findings identified in 83% of patients studied by CMA. In 75% of patients with normal karyotype, one or more aberrations were detected. The most common submicroscopic aberration involved CDKN2A/2B. Prognosis was either changed or enhanced in 66% of the cases. CMA enhances the genetic profiling of pediatric B-ALL patients. Abstract: Acute Lymphoblastic Leukemia (ALL) is a malignancy of the immature lymphoid cells mainly associated with numerical and structural chromosomal aberrations. The current standard for profiling the diverse genetic background comprises a combination of conventional karyotype and FISH analysis for the most common translocations, albeit with many limitations. Chromosomal Microarray Analysis (CMA) is a high throughput whole genome method that is gradually implemented in routine clinical practice, but not many studies have compared the two methods. Here we aim to investigate the added benefits of utilizing the high resolution 2 x 400 K G3 CGH + SNP CMA platform in routine diagnostics of pediatric ALL. From the 29 bone marrow samples that were analyzed, CMA identified clinically relevant findings in 83%, while detecting chromosomal aberrations in 75% of the patients with normal conventional karyotype. The most common finding was hyperdiploidy (20%), and the most common submicroscopic aberration involved CDKN2A/B genes. The smallest aberration detected was a 9 kb partial NF1 gene duplication. The prognosis of the patients when combining conventional cytogenetics and CMA was either changed or enhanced in 66% of the cases. A rare duplication possibly indicative of a cryptic ABL1-NUP214 fusion gene was found in one patient. We conclude that CMA, when combined with conventional cytogenetic analysis, can significantly enhance the genetic profiling of patients with pediatric ALL in a routine clinical setting.